Descentralización macrorregional estratégica para el desarrollo sostenible del Perú (1979-2014) - Ramírez Miranda, Durga Edelmira (2018)
It is determined that the Macro Region conceived as an extensive transverse territorial unit is a solution for the sustainable development of Peru. It is identified that the regulation of territorial delimitation for regionalization is ineffective. The centralized allocation of the royalty does not allow for the equitable and sustainable development of regional governments. It is shown that the Macro Region, is a geopolitical subdivision that covers several regions favoring both economically and socially. It establishes that the regulatory framework is indispensable.